Needs Analysis of a PhD Program Concatenated with a Professional Master’s in Landscape and Rural Tourism in Mexico - Obdulia Baltazar-Bernal (Education Sciences)
This study presents a needs analysis for creating a PhD in Sciences concatenated with the Professional Master’s in Landscape and Rural Tourism at the Colegio de Postgraduados, Mexico. Using a qualitative approach based on documentary analysis and the mapping of 24 PhD programs across Mexico (8), Ibero-America (8), and North America/Europe (8), the research identified a gap in postgraduate education. The comparative analysis revealed that existing programs focus primarily on either conservation or territorial planning, rarely integrating rural tourism perspectives. Key findings show that Ibero-American programs emphasize natural resource management and flexible curricula, while North American and European programs offer approaches in landscape governance but lack rural tourism integration. Based on these findings, five fundamental training axes were defined: (1) research methodology, (2) conservation and management of natural resources, (3) territorial planning and rural development, (4) rural landscape economy, and (5) interdisciplinary approaches. The proposed program seeks to strengthen applied scientific training while responding to Mexico’s educational system transformations. This concatenated PhD will contribute to generating innovative knowledge for sustainable rural landscape development, consolidating CP as a reference institution in this emerging field.